Corruption and cooperation - Justin Buffat; Julien Senn (University of Zurich, Department of Economics, 2017)
Corruption is a widespread phenomenon. Nevertheless, causal evidence on the effects of corruption is still lacking. In this paper, we assess whether and how corruption affects cooperation using a public good game experiment. Overall, contributions to the public good are reduced by 30% when participants have the possibility to bribe the punishment authority. Two concurrent channels lead to lower levels of cooperation. First, the punishment of low contributors decreases both at the intensive and the extensive margin. Second, bribery discourages initially high contributors, who gradually decrease their contributions down to the level of initially low contributors.
Keywords: C91; D73; K42; 330; Corruption; bribery; cooperation; public good; institutions